2010
DOI: 10.1111/j.1743-498x.2010.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of levels of depression in medical and non-medical students

Abstract: Significant levels of depression were reported by both medical and non-medical students. Potential vulnerability factors included: a personal or family history of depression, point of degree entry and belonging to an ethnic minority. The reluctance of students to consult their tutors about such problems highlights the potentially stigmatising nature of depression, and reinforces the need for higher education institutions to address these issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 13 publications
8
55
2
4
Order By: Relevance
“…Remarkably, the frequency of clinical depressive symptoms among female students ranges from 25% to 46%, whereas lower frequency is commonly observed among male students; ranging from 12% to 34% [13,16,24,25]. The consistency of research findings could support the idea that universality does not only apply on consumed goods, but also on sentiment and general mental health status in specific populations [26].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Remarkably, the frequency of clinical depressive symptoms among female students ranges from 25% to 46%, whereas lower frequency is commonly observed among male students; ranging from 12% to 34% [13,16,24,25]. The consistency of research findings could support the idea that universality does not only apply on consumed goods, but also on sentiment and general mental health status in specific populations [26].…”
Section: Discussionmentioning
confidence: 93%
“…It is worth noting, however, that the most common symptoms of depression in people with a family history appear in both the student and the general population. Many researches pointed out that depression was more frequent in students who had a family history of it compared with those who did not [6,25,54], and identified results similar to the present study supporting that students with a family history of depression are up to 2.5 times more likely to have depression compared with those with no family history [55]. Our results may be explained with the genetic epidemiology data suggesting that younger age of onset is associated with family history of depression [56].…”
Section: Discussionmentioning
confidence: 99%
“…O histórico pessoal ou familiar de depressão compõe grupo de risco para apresentar grave quadro depressivo, constituindo-se em fator de proteção ter realizado graduação prévia (Honney, Buszewicz, Coppola, & Griffin, 2010). O sexo feminino, histórico de depressão, a não participação em atividades sociais, as dificuldades de relacionamento e a falta de atividades de lazer foram associados à maior chance de quadros depressivos (Guerrero López et al, 2013;Kim & Roh, 2014;Pucci, Rech, Fermino, & Reis, 2012;Roh et al, 2010).…”
Section: Introductionunclassified
“…In contrast Honney et al (2010) at University College London reported 32.4%, 10.8% and 5.6% of students in all year groups had mild, moderate or severe depression respectively. However both studies had numerous limitations.…”
Section: Dear Sirmentioning
confidence: 93%